Identifying Factors Affecting Doctors to Adopt Internet-Based Healthcare Application Using Extended TAM - Dreheeb, Abdul Hakim Moawia (2006)
Technology Acceptance Model (TAM) has been developed to explain user acceptance of new information technologies. The objective of this study is to identify factors that affect doctors' adoption of and the reasons of not adopting the internet-based healthcare applications. A survey was carried out that involved 300 doctors in the Alor Setar General Hospital (ASGH) in Malaysia, in order to see whether TAM fits in the health field. In addition, they survey was done to identifying factors affecting doctors in adopting the internet-based healthcare application. The core perception variables are perceived ease of use, perceived usefulness, and perceived behavior include, which include a strong determinant of intention to use. The factors identified in this research are (job relevance, output quality, result demonstrability, image, experience, subject norm, learn ability, screen design, self efficacy, support, training, and availability). From the survey, it were found that all factors have influence on doctors in adopting the internet-based healthcare application. This proved that extended TAM is important. In summary, the findings presented in the study suggest various reasons of why doctors do not adopt the internet based healthcare application in their work. Finally, some recommendations are made for the government in improving the internet-based application in the health field.